Apolipoprotein A-1-related amyloidosis 2 case reports and review of the literature. Issue 39 (September 2017) - Lu, Chunlei; Zuo, Ke; Lu, Yinghui; Liang, Shaoshan; Huang, Xianghua; Zeng, Caihong; Zhang, Jiong; An, Yu; Wang, Jinquan
Abstract: Rationale: Apolipoprotein A-1 (ApoA-1)-related amyloidosis is characterized by the deposition of ApoA-1 in various organs and can be either hereditary or nonhereditary. It is rare and easily misdiagnosed. Renal involvement is common in hereditary ApoA-1 amyloidosis, but rare in the nonhereditary form. Patient concerns: We reported two cases with ApoA-1 amyloidosis, a 64-year-old man suffering from nephrotic syndrome and a 40-year-old man with nephrotic syndrome and splenomegaly. Renal biopsies revealed glomerular, interstitial and vascular amyloid deposits and positive phospholipase A2 receptor staining in the glomerular capillary loop in case 1, and mesangial amyloid deposits in case 2. Diagnoses: After immunostaining failed to determine the specific amyloid protein, proteomic analysis of amyloid deposits by mass spectrometry was performed and demonstrated the ApoA-1 origin of the amyloid. Genetic testing revealed no mutation of the APOA1 gene in case 1 but a heterozygous mutation, Trp74Arg, in case 2. Case 1 was thus diagnosed as nonhereditary ApoA-1 associated renal amyloidosis with membranous nephropathy, and case 2 as hereditary ApoA-1 amyloidosis with multiorgan injuries (kidney and spleen) and a positive family history. Interventions: Case 1 was treated with glucocorticoid combined with cyclosporine. Case 2 was treated with calcitriol and angiotensin converting enzyme inhibitors. Outcomes: Two cases were followed up for 5 months and 2 years, respectively; and case 1 was found to have attenuated proteinuria while case 2 had an elevation of cholestasis indices along with renal insufficiency. Lessons: Proteomic analysis by mass spectrometry of the amyloid deposits combined with genetic analysis can provide accurate diagnosis of ApoA-1 amyloidosis. Besides, these 2 cases expand our knowledge of ApoA-1-related renal amyloidosis.